Aktivitas Fisik Saat Istirahat, Intensitas Penggunaan Smartphone, dan Kejadian Obesitas Pada Anak SD Full day School (Studi di SD Al Muslim Sidoarjo) - Sakinah Ramadhani; Luki Mundiastuti; Trias Mahmudiono (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2018)
Background: obesity prevalence in elementary school student increased due to low physical activity rate also excessive food intake. The habit of watching tv, using computer and smartphone is also related to this obesity prevalence.Objective: Analyze physical activity at recess, intensity of smartphone use, and incidence of obesity among students at Full Day Elementary SchoolMethod: Using a case control with 110 elementary school children consisting of two groups, namely the normal nutritional status group of 55 respondents and the obesity status group of 55 respondents.Sampling was done by propotional random sampling. This study will compare physical activity at rest, and the intensity of smartphone use on obesity status and normal nutritional status. Analysis of this study data using chi-square test and logistic regression.Results : The results showed that there was a relationship between physical activity during the first break with obesity (p=0.010) and an OR value of 0.059 with a 95% CI (0.011-0.509) which meant that students who did physical activity first break by sitting at risk 0.059 times less to be obese. As for physical activity at the second rest (p=0.748), intensity of smartphone usage during weekdays (p=0.225), and intensity of smartphone use when there was no correlation with the incidence of obesity.Conclusion: Physical activity at the first break was related to the incidence of obesity in elementary school children Full Day School. As for the second resting activity, the intensity of smartphone usage during weekdays and weekends is not related to the incidence of obesity in elementary school children Full Day School.ABSTRAKLatar Belakang: Peningkatan obesitas disebabkan kurang melakukan aktivitas fisik dan kelebihan asupan makanan. Kebiasaan menonton tv, bermain komputer, dan smartphone yang dikaitkan dengan prevalensi obesitas saat ini.Tujuan: Menganalisis hubungan aktivitas fisik saat istirahat dan intensitas penggunaan smartphone, pada anak dengan status obesitas dan status gizi normal di SD Full Day School.Metode: Mengunakan case control dengan 110 anak Sekolah Dasar yang terdiri dari dua kelompok yaitu kelompok status gizi normal sebanyak 55 responden dan kelompok status obesitas sebanyak 55 responden. Pengambilan sampel dilakukan dengan propotional random sampling. Penelitian ini akan membandingkan aktivitas fisik saat istirahat, dan intensitas penggunaan smartphone pada status obesitas dan status gizi normal. Analisis data penelitian ini menggunakan uji chi-square dan regresi logistik.Hasil: Hasil penelitian menunjukkan bahwa terdapat hubungan antara aktivitas fisik saat istirahat pertama dengan obesitas (p=0,010) dan didapatkan nilai OR sebesar 0,059 dengan CI 95% (0,011-0,509) yang berarti bahwa siswa yang melakukan aktivitas fisik istirahat pertama berisiko 0,059 kali lebih kecil untuk mengalami obesitas. Sedangkan untuk aktivitas fisik saat istirahat kedua (p=0,748), intensitas penggunaan smartphone saat weekdays (p=0,225), dan intensitas penggunaan smartphone saat weekend (p=0,246) tidak terdapat hubungan dengan kejadian obesitas.Kesimpulan: Aktivitas fisik saat istirahat pertama berhubungan dengan kejadian obesitas pada anak SD Full Day School. Sedangkan untuk aktivitas istirahat kedua, intensitas penggunaan smartphone saat weekdays dan weekend tidak berhubungan dengan kejadian obesitas pada anak SD Full Day School.